Extraordinary Renditions and the Humanitarian Acquis of International Law. Does the New American Administration open up any Prospects for Change? - Salmón, Elizabeth (2009)
This paper addresses the figure of "extraordinary renditions" developed by the United States after the attacks of September 11, 2001. To do so, the author presents an approach on the notion of extraordinary renditions. She then discusses the presence of military bases outside U.S. territory, which have allowed the United States to develop its anti-terrorist policy, and analyzes the implications of International Humanitarian Law (IHL) in this so-called "war on terrorism". Likewise, in the context of human rights, the author analyzes whether human rights instruments are applicable in these contexts and the obligations of International Human Rights Law (IHRL) that are being violated by the extraordinary renditions. Finally, some reflections are presented on the path that the new administration should follow in order to make its anti-terrorist policy compatible with the humanitarian acquis of contemporary international law.